An assessment of tree species dynamics in rural farmland of Nepal - Kharal, DK; Oli, BN (Banko Janakari, 2009)
Dynamics of species distribution, species composition and species number are very important areas to be understood for sustainable management of forest and tree resources. The paper endeavours to solicit information on dynamics of tree species in terms of their composition and number, and also assesses the relationship between socio-economic factors and tree species dynamics. The study was conducted through survey of 98 sampled households, focus group discussion and direct field observation. Species composition and species number of tree resources of the study area are identified for different time period. The study found out that proportion of tree species loss on farmland was higher than that of species introduction. Similarly, 20 species were found with very limited distribution in the study area while two of them are already under the threatened category at the national level. The reasons for species change in the farmland are also identified. Farmers are now attracted to grow fast growing, multipurpose and easily available tree species. Economic return is the major concern for them. Such a situation may lead to further loss of tree species from the farmland. Some species such as Shorea robusta and Phyllanthus emblica, which were among the widely distributed in the beginning, are now about to be lost because of easy availability in nearby forest, slow growth rate and limited uses. Key Words: Composition, Diversity, Dynamics, Farmland, Socioeconomic factors, Trees. doi: 10.3126/banko.v17i2.2150 Banko Janakari, Vol. 17, No. 2, 3-10